The Concept Of Adultery Post-Revision Of The Penal Code - M. Junaidi; Resky Gustiandi Candra Imansyah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Zina is an act that is prohibited by religion as well as by the state. Adultery is arranged in two rules; in Indonesia it is regulated in the Criminal Code called KUHP. For the case of adultery, it uses offense complaint, which means that it will only be processed criminal law if there is one spouse who reported this legal event. While in Islam, zina actions are regulated in the Qur'an and Hadith. The problems appeared when the article that regulates zina in the existing criminal code law will be revised its offense from the offense complaint becomes a general offense. This research is under normative research. The type of data in this study is secondary data which were collected by the study method library. The data collected were analyzed by qualitative descriptive method. The result shows that in the Islamic context of adultery, the reporting and proofing process requires only 4 witnesses and it must be seen by firsthand. Whereas in the draft amendment of the criminal law, the adultery will be regulated by general offense resulting in the proof that should be studied not only from the sociological aspect but also the theological aspect.